Disease reaction of some traditional rice germplasm against important diseases of rice under gangetic alluvial region of West Bengal - S.K. RAY and S. PAL, R. MANDAL*, R. DAS, S. DUTTA (Indian Phytopathology, 2016)
Rice crop is affected by number of fungal, bacterial and viral diseases. Among the different fungal diseases false smut and sheath rot are considered to be the emerging diseases causing considerably losses in rice production in gangetic alluvial region under changing climate condition. Keeping the fact in mind, an experiment was conducted at RRSS, Chakdah, Bidhan Chandra Krishi Viswa Vidyalaya, in kharif 2015 to find out the resistant / tolerant traditional germplasm against these diseases under natural infection condition. Among the twenty eight germplasm evaluated, 78 per cent exhibited resistant reaction and may be exploited in future as resistant source against false smut disease, while 22 per cent of the germplasm showed moderately susceptible reaction, respectively against false smut disease. Majority of the germplasm exhibited tolerant to moderately susceptible reaction under natural condition, whereas 10 per cent of the germplasm showed moderately susceptible reaction against sheath rot disease. About 17 per cent of the germplasm exhibited moderately susceptible reaction against neck blast disease of rice.